Cortisol as a reliable indicator of stress in alpacas and llamas - Arias C., Nino (2015)
Research papers on the measurement of cortisol and its metabolites in alpacas and llamas were reviewed. Plasma, serum, saliva cortisol and fecal cortisol metabolites concentrations increase after stress events. The interpretation of these results should be complemented with additional physiological signs and behavioral observations.